INTEREST GROUP AND LOBBYING IN INDIA - K C, Suresha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Interest groups are the intermediate agency between people/society and the state; they carry the interests of the people and pressurise the state to fulfil the same. The methods that they use to pressure the state to fulfil their interests are called lobbying. This paper tries to understand the nature and mechanism of Interest Groups and the methods they employ to lobby for fulfilling their demands.